PENGARUH KONFLIK TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN (PERSERO) MANADO - TIDAJOH, MIRACLE GLANDY; Areros, William A.; Tarore, Henny S. (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
Conflict comes from the Latin verb configere which means to hit each other. Sociologically,conflict is defined as a social process between two or more people (or groups) where oneparty attempts to remove the other by destroying it or making it powerless. The purpose ofthis study is to determine the effect of conflicts that occur in the performance of employees atPT. Pegadaian (Persero) Manado samples taken as many as 30 respondents. Data collectionmethods used are questionnaires, interviews, and documentation. Data were analyzed usingdescriptive research method of research that is research which combine between qualitativeand quantitative method. In this research, the result of simple correlation shows strongcorrelation or influence between conflict variable and performance equal to 0,87% and basedon that calculation hence sought the amount of contribution of conflict to performance withresult of 75,69%. And in this research the authors get the result of conflict impact terhadapaemployee performance that has a positive impact. The conclusion of this research result showsthe reality of Manado Pegadaian employees handling and managing employees conflicts doneefficiently and effectively then positive impact will arise through the behavior that is seen byemployees as potential human resources with various consequences such as improving order,discipline in using work time, increasing productive cooperative relationship, work motivation.And suggestions to try to improve or sustain the application of existing conflicts through theapplication of a conscious presence of role conflict, accepting the conditions and stressfulsituations in work caused by the conflict, trying to be able to tolerate conflict, will have animpact on the improvement of employee performance.Keywords : Conflict, Employee Performance